Phase transitions in the lattice model of intercalation - Mysakovych, T.S.; Krasnov, V.O.; Stasyuk, I.V. (Condensed Matter Physics, 2008)
The lattice model which can be employed for the description of intercalation of ions in crystals is considered in this work. Pseudospin formalism is used in describing the interaction of electrons with ions. The possibility of hopping of intercalated ions between different positions is taken into account. The thermodynamics of the model is investigated in the mean field approximation. Phase diagrams are built. It is shown that at high values of the parameter of ion transfer, the phase transition to a modulated phase disappears.